Estimating Coconut Production and Productivity of Local Tall in Taliabu Island Using Drone and Sampling Population - Novarianto, Hengky (International Coconut Community Journal, 2022)
The objective of this research is to know the local tall coconut population, production and productivity in Taliabu Island, North Maluku Province, which is crucial for the industry. The aerial photography method using drones has been carried out to determine the distribution of coconut diversity, palm age, production potential and local coconut productivity. Production data and coconut fruit components were carried out on 6 sample populations. The result (Arvitech) revealed that in Jorjoga, the area under coconut was 335 ha out of the surveyed area of 1,066 ha. The total number of coconut palms was 55.728 palms. The Geomac survey carried out in Tabona indicated there were 77,629 coconut palms in an area of 1,000 ha. The fruit component analysis showed the weight of the whole fruit and the fruit without husk at the Jorjoga was 1,340-1,629g/fruit, and 805-1,033g/seed nut, and in Tabona was 1,478-1,577g/fruit and 944-966g/seed nut. The coconut production potential at Jorjoga was 9,539 nuts/ha/year, higher than that of Tabona with 7,227 nuts/ha/year. The coconut production and productivity estimation information can be used to develop a coconut replanting and rehabilitation strategy wherein selected varieties with good attributes for the tall coconut can be planted and ensure their proper maintenance, thus can be used to estimate the need for raw materials required for the establishment of the coconut industry in Taliabu Island. Determining the coconut population status can increase the production and productivity of coconut palms through rejuvenation, rehabilitation and expansion of coconut plantations using superior tall coconut seedlings.